2018
DOI: 10.3324/haematol.2018.206797
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib dose reduction in major molecular response of chronic myeloid leukemia: results from the German Chronic Myeloid Leukemia-Study IV

Abstract: Standard first-line therapy of chronic myeloid leukemia is treatment with imatinib. In the randomized German Chronic Myeloid Leukemia-Study IV, more potent BCR-ABL inhibition with 800 mg (‘high-dose’) imatinib accelerated achievement of a deep molecular remission. However, whether and when a de-escalation of the dose intensity under high-dose imatinib can be safely performed without increasing the risk of losing deep molecular response is unknown. To gain insights into this clinically relevant question, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Many of these adverse events resolve over time or after a brief drug holiday. A dose reduction may be considered in patients who achieved an MMR [50].…”
Section: Imatinibmentioning
confidence: 99%
“…Many of these adverse events resolve over time or after a brief drug holiday. A dose reduction may be considered in patients who achieved an MMR [50].…”
Section: Imatinibmentioning
confidence: 99%
“…However, it has not been confirmed that a full dose is necessary in all patients, when the dose is adapted to tolerance. [70][71][72] Because the relationship between the dose and the response can easily be monitored, the panel agreed that greater flexibility should be allowed for the use of TKIs at a reduced dose, 73 so that in a patient who cannot tolerate the standard full dose, but has achieved an optimal response, the TKI dose should not be increased.…”
Section: Tkis: Dosementioning
confidence: 99%
“…Some clinical trials, e.g., the German CML IV Study, have assessed doses of imatinib higher than the standard 400 mg daily to improve efficacy [1]. Of 422 patients randomized to the high-dose imatinib arm in the CML IV study, 68 reduced to imatinib 400 mg daily after achieving MMR [49]. Sixty-one of 68 remained in MMR after dose reduction, 5/68 transiently lost MMR, but regained this while continuing on imatinib 400 mg daily.…”
Section: Introductionmentioning
confidence: 99%